2020
DOI: 10.18632/oncotarget.27602
|View full text |Cite
|
Sign up to set email alerts
|

The role of EGFR mutations in predicting recurrence in early and locally advanced lung adenocarcinoma following definitive therapy

Abstract: Introduction: Roughly one third of new non-small cell lung cancer (NSCLC) is diagnosed at early stages. While lobectomy can improve mortality in this group, about 30-55% of patients will experience disease recurrence. Increased investigation into the factors affecting recurrence, particularly tumor molecular genetics such as EGFR mutations, is needed. Materials and Methods: We conducted a single-center retrospective study of 282 patients with early or locally advanced lung adenocarcinoma, with or without EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…Notably, most studies were small, retrospective, single-center studies with heterogenous populations. Our findings agree with the results of previous studies that have demonstrated that resected EGFR-positive NSCLC was associated with similar, if not higher, recurrence risk compared with wildtype EGFR NSCLC, regardless of EGFR subtype, 4 , 13 , 15 although this did not translate into poorer OS. Significant advances in targeted therapies in treatment of metastatic EGFR-positive NSCLC has likely contributed to the improved OS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, most studies were small, retrospective, single-center studies with heterogenous populations. Our findings agree with the results of previous studies that have demonstrated that resected EGFR-positive NSCLC was associated with similar, if not higher, recurrence risk compared with wildtype EGFR NSCLC, regardless of EGFR subtype, 4 , 13 , 15 although this did not translate into poorer OS. Significant advances in targeted therapies in treatment of metastatic EGFR-positive NSCLC has likely contributed to the improved OS.…”
Section: Discussionsupporting
confidence: 92%
“…A smaller study from Chicago, Illinois, reported 142 patients with EGFR-positive NSCLC contrasted against 140 patients with wildtype EGFR NSCLC and found no difference in 5-year recurrence rates, although patients with EGFR-positive NSCLC had higher rates of metastatic recurrence. 4 Mature survival outcomes were not reported owing to insufficient follow-up. Approximately three-quarters of patients in both studies had stage 1 cancer, and recurrence patterns, including timing and sites of recurrence, among those with EGFR-positive NSCLC relative to those with wildtype EGFR have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In a Korean retrospective study, patients with EGFR mutation showed shorter PFS compared with those without EGFR mutation, and the brain was the most common site of distant metastasis in patients with stage III non-squamous NSCLC who underwent CCRT (24). In another retrospective study, the metastatic recurrence rate was significantly higher in NSCLC patients with EGFR mutation than those with wild-type EGFR, especially in stage I patients who underwent definitive surgery (25). In the present trial, compared with wild-type EGFR, EGFR mutation was significantly associated with a higher recurrence rate and shorter median DFS.…”
Section: Discussionmentioning
confidence: 97%
“…Besides the molecular mechanism mentioned above, EGFR mutations have been associated with a higher risk of systemic recurrence and a worse PFS after definitive treatment in patients with stage I to III NSCLC (24,25). In a Korean retrospective study, patients with EGFR mutation showed shorter PFS compared with those without EGFR mutation, and the brain was the most common site of distant metastasis in patients with stage III non-squamous NSCLC who underwent CCRT (24).…”
Section: Discussionmentioning
confidence: 99%
“…Locally advanced lung cancer has a high recurrence rate, even after curative treatment with chemotherapy or radiation (41). In one study using stereotactic body radiation for inoperable localized non-small cell lung cancer, the three-year disease-free survival rate was only 48.3% (42).…”
Section: Discussionmentioning
confidence: 99%